A Multi-Disciplinary Review of Current Sea-Level Rise Research in Florida - Anna Cathey Linhoss; Lisa Gardner Chambers; Kevin Wozniak; Tom Ankersen (EDIS)
Sea-level rise is an issue of paramount importance for the state of Florida due to its lengthy coastline, low relief, high coastal population density, ecologically and economically vital beaches, estuaries, and wetlands, and porous limestone geology. The rate of sea-level rise in Florida generally follows the global average (~3 mm per year) and is slowly gaining public attention as a significant threat to the natural and socioeconomic future of the state. This 18-page multi-disciplinary review provides an annotated bibliographic summary of current peer-reviewed literature regarding sea-level rise in Florida. Written by Anna Cathey Linhoss, Lisa Gardner Chambers, Kevin Wozniak, and Tom Ankersen, and published by the UF Department of Sea Grant, February 2013.